(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
Nulliporites bombicoides Sacco, 1888 and Nulliporites stellaris Sacco, 1888 from the Oligocene - Lower Miocene deep-sea turbiditic sediments of Liguria and Piedmont (Monastero and Rocchetta formations) appear to belarge, agglutinated astrorhizid foraminiferids both assigned in this study tothe genus Astrorhizinoides Stschedrina, 1969 under a single species, Astrorhizinoides bombicoides (Sacco, 1888). This foraminiferis characterized by a simple, straight to slightly curved or rarely branched test, which displays a thick, smooth, finely agglutinated wall, with constrictions, and a very thin chamber lumen, whose apertures are observed at least at one of the terminal ends of the test. The tests, partly crushed, are preserved mostly on the soles of thin turbiditic sandstones, where they may be aligned. Probably, the foraminifer was originally a semi-infaunal, free-standing form, the test of which was partly flexible.